Perubahan Iklim sebagai Threat Multiplier dalam Ancaman Keamanan di Nigeria: Peran Kemiskinan dalam Rekrutmen Kelompok Bersenjata - Najla Khaira Syabila Tonni (Indo Publishing, 2026)
Climate change has evolved into a multifaceted threat to climate security, no longer merely an environmental threat or simply an environmental issue. This study examines how climate change affects Nigeria’s internal security vulnerabilities. These internal security vulnerabilities are exacerbated by climate change. The study examines the causal relationship between conflict dynamics and ecological degradation using qualitative methodology and literature analysis. The findings reveal how the agricultural sector (the foundation of Nigerian society and economy) has been devastated by natural disasters such as the shrinking of Lake Chad and prolonged droughts. The resulting loss of livelihoods has led to forced migration, mass unemployment, and structural poverty. The loss of livelihoods has led to forced migration, mass unemployment, and structural poverty. Armed groups, particularly Boko Haram, have exploited this extreme economic hardship by offering monetary incentives as a recruitment tool. Rather than directly causing violence, climate change exacerbates instability by making existing poverty and socioeconomic vulnerabilities far more severe.